The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1063/1.478834
|View full text |Cite
|
Sign up to set email alerts
|

Structures and energetics of the water heptamer: Comparison with the water hexamer and octamer

Abstract: In spite of a spate of studies of various water clusters, a few theoretical studies on the water heptamer are available. State-of-the-art ab initio calculations are thus carried out on twelve possible water heptamer structures to explore the conformation as well as spectroscopic properties of this water cluster. Two three-dimensional cagelike structures comprised of seven-membered cyclic rings with three additional hydrogen bondings were found to be the lowest-lying energy heptamer conformers. The global minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
0
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(94 citation statements)
references
References 69 publications
7
83
0
4
Order By: Relevance
“…Shields et al 70 applied Eq. (6) at the MP2/ADZ//MP2/6-31G* level and Richard et al used the 1 /2-1 /2 mixing ratio at MP2/AVXZ (X = D, T, Q, 5), 94 while Kim et al 54 reported that the average of the uncorrected and BSSE-corrected binding energies "is nearly invariant to the basis sets larger than TZ2P++ for the water hexamer." The contribution of the present study consists of the fact that the mixing ratio between D e and D e CP (previously suggested in a heuristic manner) is determined via a least-mean-squares approach from a larger dataset that encompasses clusters of various sizes.…”
Section: A Validation Using the Results For The (H 2 O) 2-68 Clustersmentioning
confidence: 99%
See 1 more Smart Citation
“…Shields et al 70 applied Eq. (6) at the MP2/ADZ//MP2/6-31G* level and Richard et al used the 1 /2-1 /2 mixing ratio at MP2/AVXZ (X = D, T, Q, 5), 94 while Kim et al 54 reported that the average of the uncorrected and BSSE-corrected binding energies "is nearly invariant to the basis sets larger than TZ2P++ for the water hexamer." The contribution of the present study consists of the fact that the mixing ratio between D e and D e CP (previously suggested in a heuristic manner) is determined via a least-mean-squares approach from a larger dataset that encompasses clusters of various sizes.…”
Section: A Validation Using the Results For The (H 2 O) 2-68 Clustersmentioning
confidence: 99%
“…50 The binding energy of the water heptamer has been reported at both the MP2 and CCSD(T) theories. Acelas et al 76 studied five different structures at the MP2/6-311++G(d,p) and CCSD(T)/6-311++G(d,p) levels, while Kim et al 54 reported ten different isomers at MP2 with similar quality basis sets. The octamer and endecamer systems have been treated with MP2 by one of us 43 employing as large basis sets as aug-cc-pV5Z.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to compare the relative stability of the clusters from the hydrogen bonding analysis and the second order difference in energy (D 2 E) analysis. As shown in Figure 2d, although there is only one HB per each water molecule in the cyclic structure of (H 2 O) [3][4][5] , the HB strength is very strong in (H 2 O) [4][5] . Therefore the second order difference in energy (D 2 E) of these two clusters, especially (H 2 O) 4 is positive.…”
Section: Energetic Stabilitymentioning
confidence: 91%
“…There are a larger number of energetically competing isomers for hexamer, including ring, book, bag, prism, cage, and boat structures [14][15][16][17][18][28][29][30][31]. For water cluster (H 2 O) n , n = 7-10, the structures are either an octamer ((H 2 O) 8 ) or derivatives of the water octamer [4][5][6][7][8]27].…”
Section: Introductionmentioning
confidence: 98%
“…There exist multiple low-lying isomers, which can be classified as Prism, Cage, and Chair conformations ( Figure 6). 50,51,189,196 A Prism structure has been calculated as the lowest energy heptamer with conventional MP2 calculations 51,196 and with RI-MP2 extrapolations to the estimated CBS limit.…”
Section: Larger Clustersmentioning
confidence: 99%